A high-efficiency continuous class-F power amplifier design using simplified real frequency technique - Md. Golam Sadeque; Zubaida Yusoff; Mardeni Roslee (Bulletin of Electrical Engineering and Informatics, 2020)
The fourth-generation (4G) wireless communication has been deployed in many countries. However, there are still some problems such as spectrum crisis due to the increase of wireless mobile devices and servicing. Therefore, the fifth-generation (5G) communication system will be employed at some different spectrum other than 4G frequency band. The radio frequency power amplifier (RFPA) is the key component of the 5G system. In this paper, a broadband continuous class-F (CCF) RFPA is designed for the 5G frequency band from 3.3-4.3 GHz. The input and output matching network are designed using the simplified real frequency technique (SRFT). Using a 10W GaN CGH40010F Cree device, the efficiency of the RFPA achieved greater than 70.7% for the whole frequency band with a maximum of 81.5%. The output power and the gain are more than 40 dBm and 10 dB respectively